Analisis Kecukupan Nafkah Kelompok Ternak Bina Insani, Dusun Cidogdog, Desa Wanasari, Kabupaten Subang - Azzah Hanifah; Ridi Arif (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
The livelihood of the people of Cidogdog Hamlet, Wanasari Village is derived from animal husbandry from agriculture. However, raising livestock is a side job of the community because farmers have small-scale characteristics. Everyday farmers breed more rice fields than take care of cows. This is because, livestock are considered to be long-term savings not as the main source of income. This study aims to determine the factors of financial constraints and livestock livelihood adequacy strategies. This research was conducted using qualitative methods. The results showed that the limited capital affected the fulfillment of the livelihoods of farmers in the Farmer Farmers' Group. Key words: adequecy, farmers breed, financial